TYPES AND FUNCTIONS OF PHRASEOLOGICAL UNITS - Avbakirova, D.N. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
The English language has a thousand-year history. During this time, a large number of expressions accumulated in it, which people found successful, accurate and beautiful. And so a special layer of the language arose - phraseology, a set of stable expressions that have independent significance. The article is devoted to the study of the types and functions of phraseological units and phraseology as a science.